Phytase-producing rhizobacteria enhance barley growth and phosphate nutrition - El Ifa, Wided; Belgaroui, Nibras; Sayahi, Naima; Ghazala, Imen; Hanin, Moez (Frontiers in Sustainable Food Systems, 2024)
Phosphorus (P) is the second most important macro-element for plant growth, and its low availability in soil is a major obstacle to crop production. Inorganic phosphate (Pi) is the least available form in the soil, while organic phosphate (Po) is the most dominant one, up to 80% of which exists as inositol hexakisphosphate, also known as phytic acid (PA) that cannot be absorbed by plant roots unless hydrolyzed by microbial phytases. Similar to phosphate-solubilizing bacteria, many plant growth-promoting rhizobacteria (PGPR) can play a relevant role in phosphate turnover. In our study, we screened a series of PGPR strains for phytase activities using PA as a sole source of P. Three strains (named C2, N4, and S10) with relatively high phytase activities ranging from 42.84 to 100.55 Units g−1 were selected for barley growth assays. When barley plants grown in poor sandy soil and irrigated with a PA-containing solution were inoculated with each of these PGPR isolates, a significant growth enhancement was observed. This positive effect was well illustrated by an increase in root growth, plant height, and chlorophyll contents. In addition, the inoculated barley plants accumulated significantly higher Pi contents in leaves and roots compared to non-inoculated plants. Finally, the expression of a number of high-affinity Pi transporter genes (PHT1.1, PHT1.4, PHT1.8, and PHT1.6) in inoculated barley plants was downregulated especially in roots, compared to non-inoculated plants. This difference is most likely due to the bacterial phytases that change the P availability in the rhizosphere. In summary, these three strains can improve barley growth under phosphate-limited conditions and should be considered in developing eco-friendly biofertilizers as an alternative to conventional P fertilizers.